Shocking Revelations of Allopathic Research for Cancer By U.S.A. Scientists! 2017. (Advancements in Homeopathic Research, 2022)
Now, at Johns Hopkins University of USA, news were published in NATURE latest issue, 2017 (1); that, “Scientists discover how cancer spreads?” This took them 2017 years. They called it “Metastasis”. Also they wrote, ‘90%’ of cancer death are caused when cancer cells break-off from the origin and start spreading elsewhere in the body’.(How &Why, Patel). Further, They wrote, surprisingly that, “THERE ARE NO EXISTING DRUGS FOR STOPPING THIS SPREAD”. (is it not more shocking for cancer patients?). Why Metastasis is/was there in the axillary glands or cervical glands or any where? What about Unknown primary cancer in the body after whole body scanning when metastasis is known? What to do? Give Radiation or remove glands? Biopsy done. Report came. What to do, now?” 90% of cancer death are caused when cancer cells break-off from the original and starts spreading elsewhere in the body. Give Chemotherapy. Why? Or Radiation to metastatic part(glands or bony part).Why? What can happen? If chemotherapy or Radiation is given within 2,3,4,5,6 months primary appears in the body (lung, breast, liver or anywhere).Now what to do? More chemotherapy or Radiation? I had/have many cases out of 50,000 cases treated by me by Homoeopathy. Such cases were palliated for long time up to ‘Survival period of 5 years’. We have in Homoeopathy medicines for primary cancer and its metastasis. Present scientists do not want to know or want to mention the name of Dr. Hahnemann, who named Homoeopathy after discovering the Law of Similars in1790. He did write, thus “I cannot therefore advise, for instance, the local extirpation of the so-called cancer of the lips, and face, or breast is removed by the knife alone and when encysted tumours are enucleated; something worse ensues, or at any rate death is hastened - the basic malady is thereby not diminished in the slightest, the preserving vital force is therefore necessitated to transfer the field of operation of the great internal malady to some more important part (as it does in every case of metastasis), and the consequence is blindness, deafness, insanity, suffocative asthma, dropsy, apoplexy, etc. How true it is at present?. (Organon of Medicine, 5th & 6th editions (2),1833 &1842, in the footnote to Para.205). Why and how metastasis takes place. It is not “densely packed cancer cells cause to produce metastasis”. Only one cell or even small fragment of cancer can migrate to other site if sensitive through nerve, blood, lymphatic channels to near by glands or distant organs or systems and the whole body and its systems. I, also wrote in my article on breast cancer (4) thus; “What is the cause of this relapse and metastasis? Was it due to incomplete surgery? May be due to the remaining fragment or fragments of the primary cancer/tumour. Was it due to superficial local removal of cancer/ tumour(lumpectomy)? Then, why not deep pectoral minor or major muscle also hoping to clear out a few fragments of the leftover of breast cancer? Is it a “radical mastectomy”? Yes. Then why metastasis take place after “radical mastectomy”? Or relapse? Is cancer hidden somewhere in the body? yes. Where?
Keywords: metastasis; surgery; fragment; organ